2021
DOI: 10.3389/fmicb.2021.744914
|View full text |Cite
|
Sign up to set email alerts
|

A Novel β-Glucosidase From Chryseobacterium scophthalmum 1433 for Efficient Rubusoside Production From Stevioside

Abstract: Graphical AbstractAs a natural sweetening and solubilizing agent, rubusoside has great potential in the application of healthy beverages and pharmaceuticals. A novel β-glucosidase CsBGL obtained here from Chryseobacterium scophthalmum 1433 through screening of the environmental microorganisms could specifically hydrolyze the C-13- or/and C-19-linked sophorese of steviol glycosides, but not the C-13- or/and C-19-linked Glcβ1-2[Glcβ1-3]Glc trisaccharide and Glcβ1-monosaccharide of steviol glycosides, and thus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Many β-glucosidases that can hydrolyze ST have been reported previously; for example, BGL1, 25 EcBgl, 26 and CsBGL 27 can catalyze conversion of ST to RU. SPGase hydrolyzed ST to produce RU, steviolbioside, steviolmonoside and SV, but the yield of SV was only 64%.…”
Section: Resultsmentioning
confidence: 92%
“…Many β-glucosidases that can hydrolyze ST have been reported previously; for example, BGL1, 25 EcBgl, 26 and CsBGL 27 can catalyze conversion of ST to RU. SPGase hydrolyzed ST to produce RU, steviolbioside, steviolmonoside and SV, but the yield of SV was only 64%.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies on the hydrolysis and modification of steviol glycosides mainly focused on ST and RA, while there were few reports on RC. It has been reported that some β-glucosidase and β-galactosidase from microorganisms hydrolyze ST and RA to STE ( Nguyen et al, 2019 ), demonstrating their ability to hydrolyze the β-glucosidic linkage of the C13 side chain and β-glucosyl ester linkage of C19 side chain ( Chen et al, 2014 ; Nguyen et al, 2016 ), although the substrate specificity of enzymes from different sources varies greatly ( Lan et al, 2019 ; Yan et al, 2021 ). Based on sequence homology, the proteins encoded by 1932, 1940, 1941, and 1944 genes belong to β-glucosidase of glycoside hydrolase family 3.…”
Section: Discussionmentioning
confidence: 99%
“…More efficient methods are the heterologous gene expression of glycosyltransferases for steviol glycosylation or the production of rubusoside from Stevia extracts by enzymatic conversion using suitable glycosidases (Figure 4). Yan et al [38] isolated a β-glucosidase from Chryseobacterium scophthalmum 1433, which converted 99% of the applied steviol glycosides into rubusoside. Industrial applications of these methods are future aims that will obviate the need for Rubus suavissimus plant culture systems.…”
Section: Rubus Suavissimusmentioning
confidence: 99%